The Effect of Salinity on the Chlorophyll Content of Wheat - Velicevici, Giancarla; Madosa, Emilian; Oproi, Eugen; Iordanescu, Olimpia; Dragomir, Petru (Journal of Central European Green Innovation, 2023)
Abiotic stress caused by salinity soil affects the development and plant growth, seed production and quality in a negative way. Salinity is an important factor influencing the quality of water. Saline stress causes negative reactions in plants both morphologically, biochemically and physiologically. The chlorophyll content is an important indicator of photosynthetic capacity of plants. Amount of chlorophyll is very influenced by nutrients reserve and by environment stress. Salinity in soil occurs as a result of the factors such as improper irrigation, lack of drainage, excessive accumulation of soluble salts. The research aims to study the behavior of an assortement of wheat varieties in terms of variability in salinity tolerance. To this end, an indirect test method for salinity tolerance, based on the determination of the influence of saline stress on chlorophyll accumulation, was pursued. Determination of chlorophyll content was performed at 7, 14, 21 days after saline stress induction. The duration of stress had the highest contribution (41.72%) to the variability of the chlorophyll content, followed by the saline (10.88%) and the varieties 7.63% respectively. At the level of the whole experiment it is observed that the chlorophyll content decreased progressively as saline stress prolongation. The change in the concentration from 200 to 240 Mm showed the highest influence on this property, materialized by a significant decrease in photosynthetic capacity. A good way to understand the plant photosynthetic regime is to determine the chlorophyll content as an indirect method. A selection criterion in screening for salt tolerance can be considered the physiological features that are positively associated with production under conditions of saline stress.